2023
DOI: 10.3389/fimmu.2023.1125759
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of neutrophil extracellular trap formation attenuates NLRP1-dependent neuronal pyroptosis via STING/IRE1α pathway after traumatic brain injury in mice

Abstract: IntroductionIncreased neutrophil extracellular trap (NET) formation has been reported to be associated with cerebrovascular dysfunction and neurological deficits in traumatic brain injury (TBI). However, the biological function and underlying mechanisms of NETs in TBI-induced neuronal cell death are not yet fully understood.MethodsFirst, brain tissue and peripheral blood samples of TBI patients were collected, and NETs infiltration in TBI patients was detected by immunofluorescence staining and Western blot. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…During CPB, the neuronal cell death induced by inflammatory factors and reactive oxygen species influenced the outcome of animals [15,19]. As a new programmed cell death mechanism, pyroptosis had been indicated to play critical role in different brain injury [44][45][46]. However, there was no study investigate the role of pyroptosis in pathology of brain injury after CPB.…”
Section: Discussionmentioning
confidence: 99%
“…During CPB, the neuronal cell death induced by inflammatory factors and reactive oxygen species influenced the outcome of animals [15,19]. As a new programmed cell death mechanism, pyroptosis had been indicated to play critical role in different brain injury [44][45][46]. However, there was no study investigate the role of pyroptosis in pathology of brain injury after CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, active MLKL promotes extracellular trap formation release for the control of methicillin-resistant Staphylococcus aureus (MRSA) infection [ 56 ]. Recently, inflammasome signalling activation primes NETosis [ 57 ], in turn, enhanced formation of extracellular trap formation can lead to increase inflammasome-mediated pyroptosis [ 58 ]. In line with these, our previous study demonstrated that MLKL protects against Clostridium perfringens infection by enhancing NLRP3 inflammasome-extracellular traps axis [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PERK can mitigate inflammation, while pyroptosis leads to the suppression of all inflammatory cytokines, as well as the downregulation of NF-κB and decreased protein expression of IL-1β and IL-18 precursors in cellular extracts (Keramidas et al, 2023). Additionally, research has documented the impact of the IRE1/XBP1 pathway on ERS-induced pyroptosis (Cao et al, 2023). A study has shown that the activation of IRE1α is markedly increased in a rat model experiencing traumatic brain injury.…”
Section: Pyroptosismentioning
confidence: 99%